O ensino de polígonos por meio de uma horta escolar - Vasconcelos, Gedneide Araújo de (2025)
The present dissertation work deals with the teaching of Polygons through geometric figures, which generated, when executed, the construction of an Educational Product called the “Teaching of Polygons in the School Garden: a guide for teachers” from the construction of a school garden. The school garden can be a potential useful didactic resource in the educational context. It can be used to teach a variety of curricular components such as: Mathematics, Science, Biology, Chemistry, Physics, Geography, Environmental Education, Food Education, among others. It can also lead students to develop skills such as teamwork, problem-solving, and leadership. From these perceptions, the investigative question of this study was ordered into: what implications can a school garden for the learning of Polygons with students of the ninth grade of Elementary School (EF) bring? The general objective is to analyze the implications of the school garden for learning Polygons with students of the ninth grade of EF. As a research methodology, the norms of Didactic Engineering (DE) were followed by an applied action research, with a qualitative approach and exploratorydescriptive objectives through the intervention of the researcher, in addition to discussing the data through discourse analysis. The results were obtained from the application of the educational product to the students of the ninth grade of the final years of the EF of the Maria Nazaré dos Santos School/RO, in which the moments of activities to be carried out during nine meetings demonstrated the importance of an ordered sequence for the teaching of Polygons, aligning an action between theory and practice, as well as interdisciplinary activities. In addition, there were indications of the construction of knowledge in the ninthgrade students who assumed, from an initial diagnosis that raised previous knowledge, the importance of explaining the content of Polygons. This showed the construction of a School Garden, supported by the intention of developing competencies and skills proposed by the BNCC for the referred theme. In addition, there was interaction and commitment to the execution of each proposed step. Furthermore, the entire sequence is a suggestive element for teachers to work on the content following the pedagogical strategies in each meeting. The educational product accompanying this dissertation is available on the Educapes platform at the following address: http://educapes.capes.gov.br/handle/capes/1174248.